GeoGebra as a Technological Tool in the Process of Teaching and Learning Geometry - Mendoza Velazco, Derling José (2020)
The objective of the study was to determine the level of understanding and characterize the type of ideal geometric thinking that teachers demonstrate in solving problems with the use of the GeoGebra software. The research was of mixed character, with sequential exploratory design. It was structured in two phases. The population was made up of 120 teachers who attended the course entitled: Innovate and transform the teaching of mathematics with GeoGebra. The virtual course was developed by the National University of Education during the period 2019–2020. In the first phase of the quantitative phase, a diagnostic questionnaire of descriptive analysis was applied. The second qualitative phase applied an analytical questionnaire on the polygons issued by the participants. The results show that the participants understood the activities in a dynamic way. To learn geometry, the level of understanding was very good when using the GeoGebra. It was possible to characterize that 15% of the participants developed a basic geometric representation without connection, demonstrating a submissive and linear style in the development of activities. 35% of the participants worked on contrasting geometric polygons, representing a constructivist design of visual variables. Finally, 50% of the participants designed axial geometric polygons, representing a higher level of complexity and totalitarian figuration. In conclusion, the software generated a great interest and motivation in the pedagogical activities. With the use of GeoGebra a level of effective understanding is acquired in the development of geometry.